Re-acculturation attitudes among adolescents from returned Portuguese immigrant families - Felix Neto (2010)
The aim of this study was to understand preferences in re-acculturation attitudes among adolescents from returned immigrant families to Portugal. The study sample consisted of 615 adolescents (mean age = 16.7 years: SD = 1.6). The mean duration of sojourn in Portugal for the sample was 8.3 years (SD = 4.5). Responses obtained from the questionnaire indicated that integration was the most preferred re-acculturation attitude for the adolescents from returned immigrant families to Portugal. Marginalization was the least preferred attitude. Different demographic, and intercultural contact factors were found to account for 18% of the explained variance in assimilation, 16% of integration. 22% of separation and 14% of marginalization. Demographic and intercultural factors emerged as significant and independent predictors of the acculturation attitudes, but globally the intercultural factors were the most important ones. Migratory plans affected the preferred re-acculturation strategies. Understanding the complex relationships between demographic, and intercultural factors, and acculturation attitudes can help the social scientist to develop and apply adequate intervention strategies and to give some suggestions for the development of adequate socio-political re-acculturation programmes.